Direct and indirect risk-taking incentives of inside debt - Stefano Colonnello; Giuliano Curatola; Ngoc Giang Hoang (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
We develop a model of managerial compensation structure and asset risk choice. The model provides predictions about the relation between credit spreads and different compensation components. First, we show that credit spreads are decreasing in inside debt only if it is unsecured. Second, the relation between credit spreads and equity incentives varies depending on the features of inside debt. We show that credit spreads are increasing in equity incentives. This relation becomes stronger as the seniority of inside debt increases. Using a sample of U.S. public firms with traded credit default swap (CDS) contracts, we provide evidence supportive of the model's predictions.
urn:nbn:de:gbv:3:2-57815
Keywords: G32; G34; 330; inside debt; credit spreads; risk-taking